1993
DOI: 10.1164/ajrccm/148.5.1258
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen Dioxide and Respiratory Illnesses in Infants

Abstract: Nitrogen dioxide is an oxidant gas that contaminates outdoor air and indoor air in homes with unvented gas appliances. A prospective cohort study was carried out to test the hypothesis that residential exposure to NO2 increases incidence and severity of respiratory illnesses during the first 18 months of life. A cohort of 1,205 healthy infants from homes without smokers was enrolled. The daily occurrence of respiratory symptoms and illnesses was reported by the mothers every 2 wk. Illnesses with wheezing or we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
60
0
2

Year Published

1995
1995
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(66 citation statements)
references
References 18 publications
3
60
0
2
Order By: Relevance
“…Dodge et al (31) found evidence that respiratory symptoms in children were related to SO2 pollution levels; the same was true in Charpin's study (18 (34) showed that there was no association between NO2 levels in the home and the occurrence of respiratory infections. There was no passive tobacco smoke exposure.…”
Section: Increase In Respiratory Symptoms Survey Datamentioning
confidence: 88%
“…Dodge et al (31) found evidence that respiratory symptoms in children were related to SO2 pollution levels; the same was true in Charpin's study (18 (34) showed that there was no association between NO2 levels in the home and the occurrence of respiratory infections. There was no passive tobacco smoke exposure.…”
Section: Increase In Respiratory Symptoms Survey Datamentioning
confidence: 88%
“…In a Japanese cohort, exposure to nitrogen dioxide was associated with an increased risk of doctordiagnosed asthma and bronchitis, but not with the incidence of these diseases [109]. Two birth cohort studies that followed 1,611 infants for 1 yr and 1,205 for 18 months, and one cohort survey including 842 children enrolled at 9-10 yrs of age did not confirm these results [109][110][111]. Reasons of these conflicting results are unknown, but the difficulties in determining real exposure to indoor nitrogen dioxide could explain them in part.…”
Section: Nitrogen Dioxidementioning
confidence: 95%
“…Although some studies (24)(25)(26)(27)(28)(29) have found adverse respiratory health effects from indoor NO 2 , other studies have failed to confirm that association (30)(31)(32)(33)(34). For example, data from the National Health and Nutrition Examination Survey III did not suggest any impact from gas stoves on pulmonary function or respiratory symptoms in adults with asthma (34).…”
Section: Indoor Nitrogen Dioxide and Asthma Morbiditymentioning
confidence: 99%